2015
DOI: 10.1007/s11051-015-3197-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional FeS nanoflakes: synthesis and application to electrochemical sensor for mercury(II) ions

Abstract: We report a facile solvothermal method to prepare troilite FeS two-dimensional nanoflakes. The morphology and size were observed by transmission electron microscopy (TEM), the intrinsic crystallography of the obtained FeS nanoflakes was characterized by powder X-ray diffraction and high-resolution TEM, and the composition was analyzed by X-ray photoelectron spectroscopy. Furthermore, the prepared FeS nanoflakes were successfully modified on an electrode to fabricate a sensor for Hg 2? detection. The electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Reproduced with permission. [ 128 ] Copyright 2015, Springer; (bottom‐right) demonstration of fabrication procedure and selectivity test of a potentiometric wearable sensor based on 2D Ni‐BDC for Ni 2+ detection. Reproduced with permission.…”
Section: D Materials Based On Ferromagnetic Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 128 ] Copyright 2015, Springer; (bottom‐right) demonstration of fabrication procedure and selectivity test of a potentiometric wearable sensor based on 2D Ni‐BDC for Ni 2+ detection. Reproduced with permission.…”
Section: D Materials Based On Ferromagnetic Elementsmentioning
confidence: 99%
“…The proposed detection mechanism of FeS nanoflakes relies on the ability of Hg 2+ to form stable HgS, which is measured through cyclic voltammetry as it converts into Hg 2 S. The sensor was applied for tap and river water analysis. [ 128 ] Furthermore, a 2D Ni‐BDC (MOF) nanosheet was utilized in a wearable sensor for the potentiometric detection of Ni 2+ ions (Figure 8). The 2D Ni‐MOF operated as the electroactive material in highly porous carbon cloth doped with nitrogen and decorated with spherical porous carbon nanoparticles as a self‐standing substrate.…”
Section: D Materials Based On Ferromagnetic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For FeX (X = Se, Te), the tetragonal phase should be more accessible to synthesis in a low Se/Te ratio environment. [ 18,32 ] We found that when the Fe/S ratio reaches 4:1, the optical images of products present a shift from hexagon to square. The proportion of t‐FeS gradually increases, and the proportion of h‐FeS decreases as the S temperature decreases.…”
Section: Resultsmentioning
confidence: 94%